MEN AND WOMEN’S LANGUAGE DIFFER (Between Social Paradigm And Psycholinguistic Approach) - Ratnawati Ratnawati (Indonesian Journal of Education Teaching and Learning (IJETL), 2022)
There are many social paradigms that generally talk about men having larger brain size than women, and men’s language is different from women’s language. These issues gradually and directly discriminate women’s status in the society. This article significantly is a response to those issues. This article discusses the phenomenon from psycholinguistic point of view by examining the differences from the anatomy of the brain. By collecting data and information from other researches and literatures, this article wants to see the differences between men’s and women’s brains and how the brain size and shape can affect their language skill in terms of language storage.